1988
DOI: 10.1007/bf01805741
|View full text |Cite
|
Sign up to set email alerts
|

Medroxyprogesterone acetate enhances spontaneous mammary tumorigenesis and uterine adenomyosis in mice

Abstract: Based on our previous findings that medroxyprogesterone acetate (MPA) significantly suppressed the formation of preneoplastic mammary hyperplastic alveolar nodules in mice, and that this suppression persisted for some time, we studied the effects of different schedules of MPA treatment on spontaneous mammary tumorigenesis and uterine adenomyosis in SHN virgin mice. Mice received a subcutaneous pellet of MPA every 2 months: I) during the limited period of 1-3 months of age; II) throughout the experiment beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 13 publications
(20 reference statements)
2
12
0
Order By: Relevance
“…In another strain of mice, in MPA-treated C3H virgin females, an increase in mammary tumor incidence was also observed [4]. In a recent paper, Nagasawa et al [5] also demonstrated that MPA increased mamma D' tumor incidence in SHN mice. This tumorigenic effect of MPA on mammary glands had already been described in beagle dogs many years ago [6,7].…”
Section: Introductionmentioning
confidence: 80%
“…In another strain of mice, in MPA-treated C3H virgin females, an increase in mammary tumor incidence was also observed [4]. In a recent paper, Nagasawa et al [5] also demonstrated that MPA increased mamma D' tumor incidence in SHN mice. This tumorigenic effect of MPA on mammary glands had already been described in beagle dogs many years ago [6,7].…”
Section: Introductionmentioning
confidence: 80%
“…Progesterone also has been implicated in the growth of carcinogen-induced (Welsch 1985) and transplantable rat mammary tumors (Robinson and Jordan 1987) as well as in spontaneous tumorigenesis of the murine mammary gland (Nagasawa et al 1988). As further support for the stimulatory effect of progestins on the mammary gland epithelium, antiprogestins were found to inhibit the growth effects of progesterone in certain experimental mammary tumors, suggesting that the proliferative actions of progesterone are mediated through the PR (Michna et al 1989).…”
Section: Mammary Gland Lobuloalveolar Development Requires Prmentioning
confidence: 99%
“…Progestins increase the incidence of spontaneous mammary tumors in dogs (Frank et al, 1979) and mice (Nagasawa et al, 1988). We found that progesterone can promote DMBA-induced mammary carcinogenesis in rats (Wiehle et al, 2007).…”
Section: Prms In In Vivo Experimental Modelsmentioning
confidence: 59%